Online Youth Communities as Agents of Socio-Political Mobilization - Anna L. Burmakina; Dmitry O. Lomekin (Виртуальная коммуникация и социальные сети)
Online communities are not only platforms for self-expression but agents of socio-political mobilization. The authors studied the potential of online communities for their impact on the youth. In this context, mobilization means encouraging young citizens to participate in social and political initiatives. Opinion makers use online communities to accumulate various types of social, network, and digital capital to implement certain socio-political actions and achieve their goals. The research revealed the regions with the most numerous and effective online youth communities in the context of social and political mobilization, as well as assessed their potential. Online communities unite young people around common interests and goals, offering new forms of interaction and participation. As the youth adapt to social changes and new digital technologies, their influence on socio-political processes increases because they are effective as information providers and organizers.